A controlled 6-month clinical trial to study the effects of a stannous fluoride dentifrice on gingivitis - Mark Mallatt (Blackwell Synergy, 2007)
Objectives: This study was conducted to assess anti-plaque and anti-gingivitis benefits of a stabilized stannous fluoride (SnF2)/sodium hexametaphosphate (SHMP) dentifrice versus a negative control. Material and Methods: This was a randomized, 6-month, stratified, single-centre, double-blind, parallel group, clinical study conducted in harmony with the guidelines for evaluating chemotherapeutic products for the control of gingivitis outlined by the American Dental Association. A stabilized 0.454% SnF2/SHMP dentifrice was tested against a commercially available negative control dentifrice. Following baseline measurements, subjects received a dental prophylaxis. Subjects were instructed to brush twice daily for 60 s using their assigned product. Efficacy measurements were obtained at baseline, 3 and 6 months post treatment using the Modified Gingival Index, Gingival Bleeding Index and the Turesky Modified Quigley-Hein Plaque Index. Oral tissue examinations were performed at all visits. Results: A total of 140 subjects were enroled and 128 completed the study. Results after 6 months showed the SnF2 dentifrice delivered a 16.9% reduction in gingivitis (po0.001), a 40.8% reduction (po0.001) in gingival bleeding, and an 8.5% reduction in plaque (p50.001) versus the negative control. Both treatments were well tolerated. Conclusions: Twice daily use of the SnF2/SHMP dentifrice over 6 months provided statistically significant anti-plaque and anti-gingivitis benefits relative to a negative control.